Effectiveness of endoscopic endonasal surgery for pituitary apoplexy: A comprehensive evaluation of presentation and clinical outcomes from a tertiary care center - Ashraf Elbadry; Azza Abdelazeez; Ahmed Hemdan; Mohamed Badran (Interdisciplinary Neurosurgery, 2024)
Background: The management of pituitary apoplexy (PA) is under debate. Therefore, we studied the clinical manifestations and neuroendocrine outcomes of PA after surgical management, as well as the efficacy and safety of the endoscopic endonasal transsphenoidal approach (EETA). Methods: This retrospective study was conducted between January 2013 and May 2021, and included 62 cases of pituitary adenoma apoplexy that were managed with EETA. Results: Data from 62 patients were analyzed with a mean age of 50.7 ± 10.9 years, 90.3 % of whom were female. On admission, most patients presented with abrupt onset severe headache and vomiting, associated with endocrine dysfunction in 43.5 % and deteriorated visual acuity in 92 %. Third nerve palsy was the most noted ocular nerve palsy. After using EETA, the adenoma was resected totally, subtotally, and partially in 59.7 %, 29 %, and 11.3 % of the cases, respectively. Postoperative improvement in visual acuity was achieved in 90.3 % of patients, unchanged in 6.5 % with vision defects, and deteriorated in 3.2 %. Endocrine dysfunction improved to 19.3 % after being 43.5 %. Six patients (9.6 %) experienced transient diabetes insipidus (DI) that responded completely to desmopressin therapy for a time, and three cases were complicated with CSF leakage after the operation, but it resolved completely. No intracranial infection, carotid artery injury, or death occurred. Conclusion: Despite the availability of alternative treatment options, the surgical intervention by EETA remains the most effective and reliable method for managing patients with PA who present with sudden visual or endocrine symptoms. EETA has been shown to result in significant improvements in both visual and endocrine function, with an acceptable complication rate that can be managed effectively in many cases. As such, EETA continues to represent the cornerstone in the management of PA and should be considered the first-line treatment option for amenable patients.